Penerapan Sistem Pendukung Keputusan Analytical Hierarchy Process (AHP) dalam Pemilihan Dosen Terbaik di Universitas HKBP Nommensen Pematangsiantar - Dortua Benjamin Pola Silitonga; Juli Antasari Br Sinaga; Debora Exaudi Sirait (CV. Creative Tugu Pena, 2024)
This research aims to apply a decision support system using the Analytical Hierarchy Process (AHP) method in selecting the best lecturers at HKBP Nommensen Pematangsiantar University. Selection of the best lecturers is an important process that can affect the quality of education and the reputation of the institution. The AHP method was chosen because of its ability to handle complex decisions involving many criteria. The results of this research show that the AHP method can provide an objective and systematic solution in determining the best lecturers based on educational, research, teaching and ethical criteria. From the results of this research using the AHP method, Dr. Juli Antasari Sinaga., M.Pd as the best lecturer with the sample taken is a permanent lecturer at FMIPA, HKBP Nommensen University, Pematangsiantar. By implementing this decision support system, it is hoped that HKBP Nommensen Pematangsiantar University can increase transparency and accountability in the process of selecting the best lecturers, as well as encourage improvements in the quality of teaching and research in the campus environment.